Functionality and structure of yellow pea protein isolate as affected by cultivars and extraction pH. (November 2020) - Cui, Leqi; Bandillo, Nonoy; Wang, Yechun; Ohm, Jae-Bom; Chen, Bingcan; Rao, Jiajia
Abstract: Pea ( Pisum sativum L.) has been a promising source of plant-based protein, but better protein functionalities are needed by the food industry. In this study, pea protein isolate (PPI) was extracted by alkaline extraction-isoelectric precipitation method, followed by spray-drying. The functional attributes of PPI, as affected by four different cultivars (Agassiz, Spider, Trapeze and ND Trial) and four alkaline extraction pH (8.5, 9.0, 9.5, 10.0), were firstly studied. Results showed that cultivars had significant impacts on the solubility, emulsifying capacity and stability, and foaming capacity and stability of PPI, while alkaline extraction pH only affected emulsifying stability, and foaming capacity and stability. The protein structural characteristics were then evaluated using sodium dodecyl sulfate polyacrylamide gel electrophoresis, size exclusion chromatography with multi-angle static light scattering, quantification of sulfhydryl/disulfide group and Fourier transform infrared spectroscopy analyses. The contents of legumin, aggregates, exposed sulfhydryl group and β-turn structure were different among PPI of different cultivars. Additionally, increasing alkaline extraction pH from 8.5 to 10.0 resulted in PPI with reduced surface tension, which contributed to their better foaming capacity and stability. Graphical abstract: Image 1 Highlights: Pea protein isolates (PPI) from different cultivars differed in functionality. The structure and composition of PPI were different among cultivars. The lower legumin/vicilin ratio, the better functionality of PPI. PPI prepared by higher alkaline extraction pH had better foaming properties.